Teaching as an act of stewardship: Theology in practice - Botha, Carolina S. (HTS teologiese studies, 2014)
The concept of stewardship has evolved from merely being significant in the financial contribution that people make towards their church to an all-encompassing decision that dictates people’s lives. It is not a feeling of urgency that someone is born with, but rather a decision and commitment made on a daily basis. Teachers thus find themselves in the perfect situation to be stewards in their classrooms on a daily basis. Furthermore, this tendency is noticed in teachers who work towards turning their schools into stewardship-driven institutions that aim to develop an environment driven by a calling to teach; therefore, theology is offered a leading role in the way the school is managed.